2006
DOI: 10.1161/circulationaha.106.624502
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Training-Dependent Development of Arrhythmogenic Right Ventricular Cardiomyopathy in Heterozygous Plakoglobin-Deficient Mice

Abstract: Background-Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited disorder that causes sudden death and right ventricular heart failure in the young. Clinical data suggest that competitive sports may provoke ARVC in susceptible persons. Genetically, loss-of-function mutations in desmosomal proteins (plakophilin, desmoplakin, or plakoglobin) have been associated with ARVC. To test the hypothesis that reduced desmosomal protein expression causes ARVC, we studied the cardiac effects of heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
238
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(253 citation statements)
references
References 33 publications
8
238
0
1
Order By: Relevance
“…13,14 Mice with heterozygous plakoglobin mutations (Jup+/−) were indistinguishable from their wild-type littermates at birth, but showed RV dilatation and dysfunction, and ventricular arrhythmias by 6 months of age. These phenotypes were exacerbated by exercise (daily swimming for 2 months), 15 supporting the impression that endurance training could accelerate disease progression among individuals with ARVD/C. Despite these findings, histologic analysis of myocardium from Jup+/− mice did not show any fibrofatty infiltration, and electron microscopy studies revealed no structural changes in the desmosomes or adherens junctions.…”
Section: Mutations Plakoglobinmentioning
confidence: 72%
See 1 more Smart Citation
“…13,14 Mice with heterozygous plakoglobin mutations (Jup+/−) were indistinguishable from their wild-type littermates at birth, but showed RV dilatation and dysfunction, and ventricular arrhythmias by 6 months of age. These phenotypes were exacerbated by exercise (daily swimming for 2 months), 15 supporting the impression that endurance training could accelerate disease progression among individuals with ARVD/C. Despite these findings, histologic analysis of myocardium from Jup+/− mice did not show any fibrofatty infiltration, and electron microscopy studies revealed no structural changes in the desmosomes or adherens junctions.…”
Section: Mutations Plakoglobinmentioning
confidence: 72%
“…Furthermore, gene-expression profiling of wild-type and heterozygous mice showed no statistical differences in gene expression patterns. 15 …”
Section: Mutations Plakoglobinmentioning
confidence: 99%
“…These recommendations are based on the evidence that exercise is associated with the development and increased severity of the ARVC phenotype both in animal18, 19 and human studies 2, 3, 4. However, whether reduction in exercise after diagnosis affects the disease trajectory is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The link between ACM diagnosis and increased risk of sudden cardiac death in the athletic population has been recognized since the early description of the disease, in both patients and animal models 3, 4. In recent years, the work of James et al5 and Sawant et al6 provided a strong quantitative set of data, further corroborated by additional studies,7, 8 showing that exercise is a major contributor to disease progression in ACM.…”
Section: Introductionmentioning
confidence: 94%